L'arbuste Calotropis procera, un épisode de son histoire dans le bassin du lac Tchad - Christian Seignobos (Revue d'ethnoécologie)
Coming initially from the desert’s margins, Calotropis procera is now progressively moving down south, owing both to anthropic diffusion and to the deterioration of the environment. Calotropis procera is credited with powers which would allegedly stem from its oddity and, as such, it is perhaps one of the most solicited plants in human history. In North Cameroon, it is used for a large number of protection rituals, trials by ordeal… and it also features prominently in traditional medicine’s recipes.